2013
DOI: 10.1021/ja410145x
|View full text |Cite
|
Sign up to set email alerts
|

Total Synthesis and Anti-Hepatitis C Virus Activity of MA026

Abstract: The first total synthesis of MA026 and the identification of its candidate target protein for anti-hepatitis C virus activity are presented. MA026, a novel lipocyclodepsipeptide isolated from the fermentation broth of Pseudomonas sp. RtIB026, consists of a cyclodepsipeptide, a chain peptide, and an N-terminal (R)-3-hydroxydecanoic acid. The first subunit, side chain 2, was prepared by coupling fatty acid moiety 4 with tripeptide 5. The key macrocyclization of the decadepsipeptide at L-Leu(10)-D-Gln(11) provide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
30
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(31 citation statements)
references
References 41 publications
1
30
0
Order By: Relevance
“…These secondary metabolites receive considerable interest for their diverse biological and ecological functions, as novel antimicrobials and as biocontrol agents for plant disease suppression . They also have potential as potent antiviral agents, as, for instance, recently illustrated for MA026, a CLP with anti‐hepatitis C virus activity …”
Section: Figurementioning
confidence: 98%
“…These secondary metabolites receive considerable interest for their diverse biological and ecological functions, as novel antimicrobials and as biocontrol agents for plant disease suppression . They also have potential as potent antiviral agents, as, for instance, recently illustrated for MA026, a CLP with anti‐hepatitis C virus activity …”
Section: Figurementioning
confidence: 98%
“…In a previous report, phage display screening revealed that the MA026-binding peptide sequence was VFDSLL, which is conserved in the first extracellular loop of CLDN1. 2 Then, MA026 was found to bind to recombinant CLDN1 protein in vitro. Because CLDN1 is an essential protein in the formation of TJ, there is a possibility that MA026 binding to its extracellular loop disrupts TJ integrity.…”
Section: Resultsmentioning
confidence: 99%
“…2 In addition, we revealed that MA026 bound with the VFDSLL peptide, the sequence of which is a part of claudin-1 (CLDN1). Because it has been reported that CLDN1 is highly expressed in hepatocytes and has an important role during the post-cell binding process of HCV entry, 3 these results strongly suggest that MA026 binds to CLDN1 and inhibits HCV entry.…”
Section: Ma026 (mentioning
confidence: 95%
“…MA026 -MA026 (Fig. 8) is a lipocyclodepsipeptide isolated from the fermentation broth of Pseudomonas sp (Shimura et al, 2013). While MA026 effectively inhibits HCV entry, the possible antiviral mechanism can be traced to the interaction between MA026 and an HCV entry receptor called claudin-1 using the phase display screening and surface plasmon resonance binding analyses (Shimura et al, 2013).…”
Section: Immuno-stimulators and Cellular Protein Inhibitorsmentioning
confidence: 99%